Parameter Design for Analyzing Factors Affecting the Production of Printed Slotted-Type Corrugated Boxes - Wageesat, Supitchaya; Angsiri, Orawan; Pradabwong, Jiraporn; Sriariyawat, Nantawut (Naresuan University Journal: Science and Technology (NUJST), 2022)
The main problem of the case study company is erratically printed colors on the surface finish of the printed image on slotted-type corrugated boxes, resulting in a high defect rate of 17.58%. This research was carried out to firstly, identify the factors that are causing the erratically printed colors, specifically from the flexographic printing process, secondly, to identify appropriate parameters to be used in the printing process, and lastly, to reduce the rate of defective printed colors to an acceptable level of no more than 10%. Experiments were conducted to investigate the influence and interaction of various parameters on the surface finish of the printed image. The results showed that the interaction between four parameters had a significant impact on the surface finish of the printed image. These were the distance between the anilox roller and the printing plate, the printing temperature, printing speed and the drying time and the viscosity of the ink used during the printing process. The appropriate level of each parameter was identified and, when those parameter values were instituted, the printing defective rate was reduced to 7.5%. Keywords: Full factorial design, slotted-type corrugated board, printed image, flexography, print quality